Degradation of Pesticides by Microorganisms, A Literature Review - Camelia Costela FASOLA (LUNGEANU); Loredana DIMA; Constanta Laura AUGUSTIN (ZUGRAVU); Maria Magdalena TUREK RAHOVEANU; Gheorghe Adrian ZUGRAVU (Communications of International Proceedings, 2021)
In the lists of potentially toxic substances, pesticides are considered to have a priority role in terms of soil and water quality monitoring. Some pesticides are compounds that cannot be degraded naturally, having a long remanence time in the environment, context in which their dangerous character is highlighted as a consequence of their accumulation potential in trophic levels.
Keywords: Degradation of Pesticides; Sustainable Development.